1987
DOI: 10.1016/0035-9203(87)90056-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of a single, pre-treatment Widal test in suspected enteric fever cases in the Philippines

Abstract: 101 patients with a clinical suspicion of typhoid or paratyphoid (enteric) fever admitted to San Lazaro Hospital, Manila, Philippines, were studied by bacteriological culture of blood, rectal swab, urine and duodenal string capsule; 35 also had bacteriological culture of bone marrow aspirate. 44 of the patients were culture-confirmed as having enteric fever; the remainder were classified as non-enteric fever cases. Analysis of the pretreatment Widal agglutination titres of all patients revealed that using as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In practice, the result from a single, acute-phase serum sample is often used, but false-negative and false-positive results are common. Knowledge of the background levels of antibodies in the local population may aid interpretation of the Widal test, and performance is best among patients with a high prior probability of enteric fever (242,243). For example, in a study from Vietnam using Widal test data from patients with typhoid fever and both febrile and healthy control participants, it was found that a cutoff titer of Ն200 for O agglutination or Ն100 for H agglutination would correctly diagnose 74% of blood culture-positive patients.…”
Section: Serologic Assaysmentioning
confidence: 99%
“…In practice, the result from a single, acute-phase serum sample is often used, but false-negative and false-positive results are common. Knowledge of the background levels of antibodies in the local population may aid interpretation of the Widal test, and performance is best among patients with a high prior probability of enteric fever (242,243). For example, in a study from Vietnam using Widal test data from patients with typhoid fever and both febrile and healthy control participants, it was found that a cutoff titer of Ն200 for O agglutination or Ն100 for H agglutination would correctly diagnose 74% of blood culture-positive patients.…”
Section: Serologic Assaysmentioning
confidence: 99%
“…3 Widal test is now regarded as inaccurate, non-specific, poorly standardized and of limited diagnostic value. [4][5][6][7][8][9][10][11] To overcome such limitations, several assays and serological tests have been developed but none is found optimal. [12][13][14] A rapid serological/biochemical test to diagnose typhoid fever accurately at an early stage is thus currently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The Widal test ideally requires both an acute and a convalescent-phase serum sample taken approximately 10 days apart, and a positive result is determined by a fourfold increase in antibody titer. However, antibody titers in infected patients often rise before the clinical onset, making it difficult to demonstrate the required fourfold rise between initial and subsequent samples for a confirmatory diagnosis [83][84][85]. Furthermore, in practice, the result of a single, acutephase serum sample is often used to help patient management and, although useful in some cases, a single serum result may be confusing in others [74,80,81,[85][86][87].…”
Section: Antibody Detectionmentioning
confidence: 99%